The TLR-M-CSF axis is implicated in increased bone turnover and curve progression in adolescent idiopathic scoliosis - Kai Sheng; Daniel G. Bisson; Neil Saran; Jake Bourdages; Christopher Coluni; Kirby Upshaw; Kerstin Tiedemann; Svetlana V. Komarova; Jean A. Ouellet; Lisbet Haglund (Arthritis Research & Therapy)
Abstract Background Facet joint osteoarthritis (OA) is prevalent in patients with adolescent idiopathic scoliosis (AIS). The most pronounced OA presents above and below the curve's apex where the intervertebral rotation is the greatest. This indicates that facet joint OA is implicated and potentially contributes to AIS progression. OA impacts both cartilage and bone and we have previously demonstrated an association between lower bone quality and more severe OA in AIS facet joints. This study aimed to further investigate the molecular mechanisms underlying cartilage–bone crosstalk in the facet joints of patients with AIS. Methods Unbiased deep RNA sequencing was performed to compare gene expression in facet joint chondrocytes of age-matched AIS patients and non-scoliotic individuals. Differentially expressed genes of interest were validated through qPCR and ELISA in a larger sample cohort. Key regulatory pathways involved in cartilage–bone crosstalk were identified through bioinformatic analysis. Functional studies were conducted by treating chondrocytes with TLR2 and TLR4 agonists, collecting conditioned media, and administering it to an in vitro osteoclastogenesis model. The expression of M-CSF, a key regulatory factor influencing osteoclast proliferation, was measured in individual facet joint cartilage samples at different spinal levels and correlated with cartilage morphological grade and 3D structural parameters extracted from spine reconstruction. Results One thousand four hundred twenty six upregulated genes were detected, and gene ontology analysis revealed a significant enrichment of the TLR pathway, and bone-regulating biological processes in AIS chondrocytes. TLR activation of AIS chondrocytes induced expression of bone-regulating factors, including M-CSF, a key regulator of osteoclast proliferation. Furthermore, secreted factors from AIS chondrocytes enhanced osteoclast proliferation and maturation, with a stronger effect observed following TLR pre-activation. Clinically, M-CSF expression was found to correlate strongly with increased OA severity and a greater degree of intervertebral axial rotation. Conclusions Together, our findings suggest that the TLR-M-CSF axis is implicated in osteoclastogenesis, resulting in increased bone turnover and may contribute to curve progression in AIS patients.